On the margins of SoTL discourse: An asian perspective - Chng, Huang Hoon; Looker, Peter (Teaching and Learning Inquiry, 2013)
The International Society for the Scholarship of Teaching and Learning (ISSOTL) began in 2004, constituted by 67 scholars, mostly from English-speaking countries located in the Western hemisphere. Since then, the world has become increasingly global and borderless, and students’ movements across continents in search a good education have meant that today’s classrooms are, in varying degrees, heterogeneous. Yet SoTL discourse—the metaphors employed, the issues identified, and SoTL methods or approaches to classroom practice—have remained largely Western in orientation. This paper describes three types of exclusions of Asian participants and perspectives in mainstream discourse on the SoTL: geographical isolation, methodological solipsism, and ideological exclusion. Through a review of the dominant scholarship, we argue that an international association like ISSOTL must take active steps to consciously acknowledge the need for alternative voices that are located outside its immediate realm and that the differences in practice, participants, and the politics of culture in locations outside the West need to be taken into consideration, or ISSOTL will risk losing relevance for a greater part of world. Or to put it more positively, ISSOTL has much to gain by paying attention to and not denying the existence of such enriching, if less familiar, perspectives.